Proceedings of the Genetic and Evolutionary Computation Conference Companion 2018
DOI: 10.1145/3205651.3205670
|View full text |Cite
|
Sign up to set email alerts
|

Search-based mutation testing to improve performance tests

Abstract: Performance bugs are common and can cause a significant deterioration in the behaviour of a program, leading to costly issues. To detect them and reduce their impact, performance tests are typically applied. However, there is a lack of mechanisms to evaluate the quality of performance tests, causing many of these bugs remain unrevealed. Mutation testing, a fault-based technique to assess and improve test suites, has been successfully studied with func-tional tests. In this paper, we propose the use of mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Indeed, the ratio of effective mutants may decrease as we add more traditional mutation operators, which is a problem taking into account the high cost of applying mutation testing. As a result of this issue, Sánchez et al [26] suggested the use of an evolutionary algorithm to guide the search towards useful traditional mutants for the refinement of performance tests.…”
Section: Traditional Mutation Operators To Address Non-functional Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the ratio of effective mutants may decrease as we add more traditional mutation operators, which is a problem taking into account the high cost of applying mutation testing. As a result of this issue, Sánchez et al [26] suggested the use of an evolutionary algorithm to guide the search towards useful traditional mutants for the refinement of performance tests.…”
Section: Traditional Mutation Operators To Address Non-functional Propertiesmentioning
confidence: 99%
“…In previous short papers [25,26], we have explored the potential benefits and limitations of the application of mutation testing at the performance level, what we called performance mutation testing (PMT). Analogously to classic mutation testing, the goal of PMT is to generate variants of the original program (performance-mutants), where each variant models a performance bug, for example, one that causes a noticeable degradation of the execution time of the program.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively large number of subjects in our data set, there are applications that require even larger numbers of defects to obtain statistically significant evaluation results. For these scenarios we envision the creation of performance mutants, along the lines proposed in recent work [10] and proposals [11], and provide insights to support the creation of performance mutants that resemble performance bugs fixed in real world projects.…”
Section: Introductionmentioning
confidence: 99%